With a mind to kill [large type] - Horowitz, Anthony, 1955-; Fleming, Ian, 1908-1964 (Horowitz, Anthony, 1955- James Bond novel., 2022)
Traveling behind the Iron Curtain, James Bond must convince the Russians, including a beautiful Soviet psychiatric analyst, that he is a double agent to infiltrate a group planning a major act of terrorism, which, if successful, will destabilize relations between the East and West.